SYNTHESIS AND ANALYSIS OF LINEAR, DISCRETE AND TIMEINVARIANT SYSTEMS, USED IN THE FIELD OF COMMUNICATIONS, USING MATLAB AND SIGNAL PROCESSING TOOLBOX: SYNTHESIS AND ANALYSIS OF LINEAR, DISCRETE AND TIMEINVARIANT SYSTEMS, USED IN THE FIELD OF COMMUNICATIONS, USING MATLAB AND SIGNAL PROCESSING TOOLBOX - Denev, Daniel; Tsankov, Tsvetoslav (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Synthesis and Analysis of Linear Discrete Time-Invariant Systems Applied in Communications Using MATLAB and Signal Processing Toolbox: The paper presents the main steps in the process of synthesizing and analyzing linear discrete time-invariant systems applied in the field of communications. The simulation results of the systems implementing pre-emphasis and de-emphasis and removing DC offset are given in the paper such as impulse responses, frequency responses and pole-zero plots using MATLAB and Signal Processing Toolbox.